2012
DOI: 10.1021/jp301680d
|View full text |Cite
|
Sign up to set email alerts
|

Location of Hole and Electron Traps on Nanocrystalline Anatase TiO2

Abstract: The defect photoluminescence from TiO 2 nanoparticles in the anatase phase is reported for nanosheets which expose predominantly (001) surfaces and compared to that from conventional anatase nanoparticles which expose mostly (101) surfaces. Also reported is the weak defect photoluminescence of TiO 2 nanotubes, which we find using electron backscattered diffraction to consist of walls which expose ( 110) and ( 100) facets. The nanotubes exhibit photoluminescence that is blue-shifted and much weaker than that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
216
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(239 citation statements)
references
References 75 publications
(127 reference statements)
22
216
1
Order By: Relevance
“…Secondly, length of isopropanol is smaller than the n-propanol, which can affect the bond length/ orientation in Ti-O-Ti three Low Temperature Synthesis of Mixed Phase Titania Nanoparticles with High Yield, its Mechanism and Enhanced Photoactivity from TiO 2 to dye. Secondly, Mercado et al, 19 systematically showed that stoichiometric variation in rutile and anatase (or mixed) phase of TiO 2 affects the electron transfer ability and hence its photo-catalytic activity. The observed variations in n-TiO 2 and i-TiO 2 have been attributed to the variation in their redox behavior (ie.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, length of isopropanol is smaller than the n-propanol, which can affect the bond length/ orientation in Ti-O-Ti three Low Temperature Synthesis of Mixed Phase Titania Nanoparticles with High Yield, its Mechanism and Enhanced Photoactivity from TiO 2 to dye. Secondly, Mercado et al, 19 systematically showed that stoichiometric variation in rutile and anatase (or mixed) phase of TiO 2 affects the electron transfer ability and hence its photo-catalytic activity. The observed variations in n-TiO 2 and i-TiO 2 have been attributed to the variation in their redox behavior (ie.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, indirect excitons would be allowed to form through the mediation of phonon modes. However, in the case of anatase TiO 2 nanosystems, their existence at room temperature has been disproven by extensive measurements [18,[47][48][49] and by the results we present in the following. As such, many-body processes such as exciton-exciton annihilation can be excluded.…”
mentioning
confidence: 77%
“…Nanocomposites dispersed in ethanol were thereafter deposited onto ITO-coated glass using the doctor blade method. 38 This photoanode electrode was then sintered at 300 °C for 30 min on a hot plate. Eosin B dye (150 µL) was added using a micropipette onto the anode electrode.…”
Section: Methodsmentioning
confidence: 99%
“…38 MWCNTs have been shown to reduce recombination rates by effectively capturing and transporting generated electrons from the titania and thus reducing recombination with generated holes. 33,54 From Fig.…”
Section: Photoluminescencementioning
confidence: 99%